2015
DOI: 10.1017/s000711451500344x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and initial metabolism of 75Se-l-selenomethionine: a kinetic model based on dynamic scintigraphic data

Abstract: Selenomethionine (SeMet) is an important organic nutritional source of Se, but the uptake and metabolism of SeMet are poorly characterised in humans. Dynamic gamma camera images of the abdominal region were acquired from eight healthy young men after the ingestion of radioactive 75 Se-L-SeMet ( 75 Se-SeMet). Scanning started simultaneously to the ingestion of 75 Se-SeMet and lasted 120 min. We generated timeactivity curves from two-dimensional regions of interest in the stomach, small intestine and liver. Dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…An alternative possibility to release of free ions in the small intestine and use of ion-specific transporters in the apical membrane of enterocytes is that the mineral crosses the apical membrane or tight junctions while still complexed. This is the case for selenomethionine and selenocysteine, which serve as Se supplements (Große Ruse et al, 2015), and is suggested to be the case for AA-mineral complexes that are on the market, assuming they reach the small intestine intact.…”
Section: Chelated and Organic Mineral Supplementsmentioning
confidence: 99%
“…An alternative possibility to release of free ions in the small intestine and use of ion-specific transporters in the apical membrane of enterocytes is that the mineral crosses the apical membrane or tight junctions while still complexed. This is the case for selenomethionine and selenocysteine, which serve as Se supplements (Große Ruse et al, 2015), and is suggested to be the case for AA-mineral complexes that are on the market, assuming they reach the small intestine intact.…”
Section: Chelated and Organic Mineral Supplementsmentioning
confidence: 99%
“…The estimation quality in terms of sample size and sampling frequency was investigated in a simulation study for a popular model in pharmacokinetics, which was motivated by a recent study (Große Ruse et al, 2015). It includes subject-specific covariate information and is linear in parameters and state.…”
Section: Discussionmentioning
confidence: 99%
“…The model under investigation provides a proof of concept of our main application of modelling electroencephalography measurements of epileptic patients, which will be done in the next section, but is also inspired from a study on selenomethionine metabolism in humans (Große Ruse et al, 2015). This multi-dimensional linear transfer model finds frequent applicability in pharmacokinetics.…”
Section: Simulation Study On the Linear Transfer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, we consider a multidimensional Ornstein-Uhlenbeck model with one covariate having two levels (e.g., treatment and placebo). This type of model is common in, e.g., pharmacokinetics, and is motivated by a recent study on Selenium metabolism in humans (Große Ruse et al, 2015). Moreover, we perform hypothesis testing on the treatment effect and investigate the performance of the Wald test.…”
Section: Introductionmentioning
confidence: 99%